Integrating ecosystem services into sustainable landscape management: a collaborative approach - Terêncio, D. P. S. (2021)
The Paiva River is considered one of the least polluted rivers in Europe and its watershed has a high conservation value. However, the Paiva River basin suffers pressures related with recurrent disturbances in land use, such as forest fires, agricultural activities, urbanization and pressures that affect the natural hydromorphological conditions and the continuity of watercourses. Blue and Green Infrastructures (BGINs) emerge to improve biodiversity, sustainability and the supply of ecosystem services while improving socioeconomic aspects. Thus, this article aims to identify priority areas in the basin, for intervention with these infrastructures. For that, a spatial multicriteria decision analysis (MDCA) was carried out according to several data related to the Paiva River Basin. As local politicians and responsible entities for the natural resources management are the main experts on the problems and their possible solutions at the local level, they were involved in this decision-making model. Therefore, these specialized stakeholders did the weighting assignment according to the most or least importance of the same for the work. The map of priority locations to implement BGINs was obtained in the sequel. To the top 5 priority areas, stakeholders attributed the best solutions based on nature. The most recommended BGINs were recovery/maintenance of riparian vegetation and conservation and reforestation of the native forest, both presented in four of the five areas, and introduction of fuel management strips presented in three of the five areas. Thus, we concluded that it is extremely important to include the communities and the competent entities of nature and environment management in scientific projects related to conservation, forming a synergy that makes it possible to combine scientific knowledge with local experience acquired in the field. This project uses a very flexible methodology of local data and can be a great example to be implemented in other hydrographic basins anywhere in the world